Efficacy of dexmedetomidine on myocardial ischemia/reperfusion injury in patients undergoing cardiac surgery with cardiopulmonary bypass: A protocol for systematic review and meta-analysis. Issue 9 (3rd March 2023) - Liang, Gencheng; Li, Yueyong; Li, Sheng; Huang, Zhaohe
Abstract : Background: Cardiac surgery using cardiopulmonary bypass has been shown to cause reversible postischemic cardiac dysfunction and is associated with reperfusion injury and myocardial cell death. Therefore, it is very important to have a series of measures in place to reduce oxygen consumption and provide myocardial protection. We performed a protocol for systematic review and meta-analysis to evaluate the effect of dexmedetomidine administration on myocardial ischemia/reperfusion injury in patients undergoing cardiac surgery with cardiopulmonary bypass. Methods: This review protocol is registered in the PROSPERO International Prospective Register of systematic reviews, registration number CRD42023386749. A literature search is performed in January 2023 without restriction to regions, publication types or languages. The primary sources were the electronic databases of PubMed, Embase, Web of Science, the Cochrane Central Register of Controlled Trials, Chinese National Knowledge Infrastructure database, Chinese Biomedical Database, and Chinese Science and Technology Periodical database. Risk of bias will be assessed according to the Cochrane Risk of Bias Tool. The meta-analysis is performed using Reviewer Manager 5.4. Results: The results of this meta-analysis will be submitted to a peer-reviewed journal for publication. Conclusion: This meta-analysis will evaluate the efficacy and safety of dexmedetomidine in patients undergoing cardiac surgery with cardiopulmonary bypass.